ОСОБЕННОСТЬ СПЕЦИФИКИ ОБЩЕНИЯ ЯЗЫКА СПЕЦИАЛЬНОСТИ В НЕФИЛОЛОГИЧЕСКОМ ВУЗЕ - Мамадалиева, Ф.А. (SCIENCE and SOCIETY, 2025)
The article examines the specifics of teaching Russian to students of exclusively economic universities and departments. Particular attention is paid to disciplines, topics and terms that are relevant and studied directly by economics students. The article examines the relationship between the Russian language and the economic sphere, identifies its role in studying important disciplines in this area and suggests ways to successfully combine this language with the specifics of the future profession of students majoring in economics.
Keywords: English; arguments; higher mathematics; discussion; discipline; theses; topics; temperament; terminology; educational material; curriculum; figures; economics